Association between alcohol consumption and allergic rhinitis in US adults - He, Yan; Xu, Yingying; Lin, Zhiqiang (Frontiers in Nutrition, 2025)
IntroductionIncreasing evidence suggests that alcohol consumption may be associated with allergic diseases. This cross-sectional analysis aimed to determine the correlation between alcohol consumption patterns and allergic rhinitis (AR) in US adults.MethodsA cross-sectional study was conducted involving 2,179 individuals aged 20 years and older who took part in the 2005–2006 National Health and Nutrition Examination Survey (NHANES), which assessed AR and alcohol consumption patterns. Alcohol consumption was categorized into three groups: “Never” (fewer than 12 drinks in a lifetime), “Now” (currently drinking), and “Former” (a prior history of drinking but no longer consuming alcohol). The association between alcohol consumption patterns and AR was analyzed separately for men and women, adjusting for several comorbidities.ResultsIndividuals who currently consume alcohol are more likely to exhibit elevated levels of total IgE and cat/dog dander-specific IgE compared to non-consumers. Compared to “Never” in the male group, “Now” (currently drinking) was positively associated with AR in both the partially adjusted analysis and the fully adjusted model. However, we did not find any positive relationship between alcohol consumption patterns and AR in the female group, which suggests that current drinking was linked to a higher prevalence of AR in men but not in women.ConclusionWe discovered that current drinking was positively associated with a high prevalence of AR in men.